2002
DOI: 10.1248/bpb.25.109
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Cultured Human Fetal Membrane Cells Infected with Influenza Virus.

Abstract: When a virus encounters a susceptible cell, the virus enters it to initiate cytocidal, persistent, latent or abortive cell infection. The influenza virus induces cytocidal infection accompanied by virus production and cell death in several types of cultures such as HeLa and Madin-Darby canine kidney (MDCK) cell lines and human peripheral blood monocytes in vitro, all of which die through the mechanism of apoptosis. 1-4)The human influenza virus usually infects the human respiratory organs. However, influenza v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(79 citation statements)
references
References 26 publications
2
74
3
Order By: Relevance
“…Interestingly, we have reported that influenza virus infection induced apoptosis and the gene expression of interleukin (IL)-6, tumor necrosis factor (TNF)-α and interferon (IFN)-β in cultured human fetal membrane chorion trophoblast cells. [12][13][14] However, even though the virus proliferated in cultured amnion epithelial cells, it should be noted that we did not observe the above phenomena in these cells. [12][13][14] Overall, these findings suggest that the induction of apoptosis and gene expression of pro-inflammatory cytokines in chorion trophoblast cells may have a possible role in the etiology of adverse pregnancy outcomes that are associated with an intrauterine infection caused by an influenza virus.…”
contrasting
confidence: 69%
“…Interestingly, we have reported that influenza virus infection induced apoptosis and the gene expression of interleukin (IL)-6, tumor necrosis factor (TNF)-α and interferon (IFN)-β in cultured human fetal membrane chorion trophoblast cells. [12][13][14] However, even though the virus proliferated in cultured amnion epithelial cells, it should be noted that we did not observe the above phenomena in these cells. [12][13][14] Overall, these findings suggest that the induction of apoptosis and gene expression of pro-inflammatory cytokines in chorion trophoblast cells may have a possible role in the etiology of adverse pregnancy outcomes that are associated with an intrauterine infection caused by an influenza virus.…”
contrasting
confidence: 69%
“…1) Chromosomal DNA in chorion cells is fragmented into oligonucleosomes by IV infection at MOIϭ4 and 40, occurring from 24 h after infection. 1) As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) Chromosomal DNA in chorion cells is fragmented into oligonucleosomes by IV infection at MOIϭ4 and 40, occurring from 24 h after infection. 1) As shown in Fig. 1, IV induced DNA fragmentation in chorion (lane 1) but not in amnion cells (lane 2) at 48 h after infection at MOIϭ40.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Infection with influenza virus type A induces leakage of LDH from cultured chorionic cells; this is accompanied by degradation typical in apoptotic cells, such as fragmentation of oligonucleosomal DNA, and condensation and fragmentation of the nucleus. 56,57 Assessing the release of intracellular LDH, which occurs because of the breakdown and alteration in the permeability of the plasma membrane, is a commonly used marker for estimating cytotoxicity. 58 Therefore, we treated A2780 cells with 50 nM GEM, 50 nM AgNPs, or a combination of 50 nM GEM and 50 nM AgNPs for 24 h and then measured the leakage of LDH.…”
Section: Combined Treatment With Gem and Agnps Enhances Cytotoxicitymentioning
confidence: 99%